Nutritional and phenolic profiles of Hibiscus cannabinus L.: Food and feed industries prospect - Tlou Christopher Kujoana; Monnye Mabelebele; William James Weeks; Freddy Manyeula; Nthabiseng Amenda Sebola (Applied Food Research)
Hibiscus cannabinus L. (kenaf) plant of the Malvaceae family is primarily a fibre crop with high in dietary proteins, fibre and bioactive phytochemicals of significant nutritional and therapeutic benefits making it a suitable alternative to the current expensive and unavailable conventional crops including soyabean. Hence, this study aimed at evaluating the nutritional and phenolic profiles of the kenaf's selected organs and their applications in food and feed industries. Five selected organs of kenaf were analysed for nutritional and phenolic compositions. Data were analysed using a Statistical Analysis System (SAS). Descriptive statistics were applied to the phenolic data, and the results were presented as they were. Tender leaves (TL) constituted higher (p < 0.05) crude protein and energy, while roots had higher (p < 0.05) crude fibre. Stems had higher (p < 0.05) ash, while TL, mature leaves (ML) and late mature leaves (LML) recorded higher (p < 0.05) calcium and phosphorus. Stems also recorded higher magnesium, whereas ML recorded the highest amounts of iron. Except for methionine, amino acids varied significantly throughout the selected organs where lysine and aspartic acid were highest (p < 0.05) in kenaf mature leaves. The ML were abundant with phenolics, followed by TL, except for LML, having most of its phenolics different from other selected organs. Therefore, current findings indicated that kenaf has high key nutrients and phenolics, implying that it has considerable health and nutritional benefits for both humans and animals, making them critical to the food, feed and health industries.